MANAJEMEN RISIKO PADA PT X MENGGUNAKAN METODE RBS DALAM PENYEDIAAN LAYANAN TELEKOMUNIKASI - Mayun, Gung (Prodi Sistem Informasi FST Universitas Jambi, 2022)
The company PT X is a provider company that has been established since 1989. One of the keys to the success of PT X can survive until now is to make a transformation that aims to provide services to customers and increase company value. In the current conditions, the telecommunications industry in Indonesia requires a broad and explicit evaluation that emphasizes business risk. To overcome these risks, while recognizing the business development opportunities that accompany them, further guaranteeing the realization of the Company's various strategic plans and ensuring business continuity, PT X applies the ISO 31000 Risk Management (